Solutions to Expansion of Import-export Financing Operations at Agribank Thanh Hoa in the Process of Participation in Free Trade Agreements - Tran Thi Thu Huong (Newinera Publisher, 2020)
This research aims to describe solutions to expansion of import-export financing operations at Agribank Thanh Hoa in the process of participation in FTAs (Free Trade Agreements). This paper presents the results of the study titled “Impacts of FTAs on Vietnam’s Economy - Finance”, clarifying the opportunities for and challenges to Vietnam’s economy - finance from joining the FTAs and influences on Vietnam’s commercial banks during the involvement in the FTAs. It also emphasizes the current situation of lending operations in Agribank-Thanh Hoa Branch (hereinafter referred to as Agribank Thanh Hoa), Complete solutions group credit activities financed import-export in Agribank Thanh Hoa, including solutions for executive management, professional solutions group credit for export financing, solutions group strategic human and banking technology and policy solutions for customers.